Total synthesis of bioactive natural products - Brahmachari, Goutam (Elsevier, 2019)
Total Synthesis of Bioactive Natural Products provides step-by-step guidelines for effectively synthesizing the most promising bioactive agents from a broad range of natural products. Beginning with a concise background that outlines the benefits and challenges faced in effective synthesis, the book goes on to provide individual outlines for approximately 100 of the most promising bioactive agents. Taking a logical, user-friendly approach, the systematic name, compound class, structure, natural source, pharmaceutical potential and synthetic routes for each structure are detailed, with clear illustrations throughout, making this book an essential and practical guide for anyone working with both synthesis and natural products.